Association of Anthropometric Parameters with Lipid Profile among Adult Population of Kaski District, Nepal - Kathayat, G.; Pokharel, D. R.; Yadav, N. K.; Manoj, S. (Kathmandu University Medical Journal, 2021)
Background Anthropometric parameters of individuals are good at predicting functional impairment, mortality, and future cardiometabolic diseases. The relationship between anthropometric parameters and lipid profiles have been studied in different parts of the world. But to date, no such studies have been conducted in Nepal. Objective To investigate the association between anthropometric parameters and lipid profile in the adult population of Kaski district, Nepal. Method This study was carried out at Manipal Teaching Hospital, Pokhara, Kaski, Nepal. The fasting lipid profiles were analyzed in a total of 400 subjects aged > 18 years with an automated OCD Vitros 350 dry chemistry analyzer. The Kolmogorov-Smirnov test was used to test the normality of the data. The mean values of fasting lipids were compared within the subjects with different body mass index groups using ANOVA and waist circumference, waist-hip ratios, waist-height ratios, and neck circumference using independent samples t-test. The anthropometric indices evaluated were body mass index, waist circumference, waist-hip ratio, waist-height ratio, head circumference, neck circumference, and mid-upper arm circumference. Pearson’s correlation coefficients and multiple regression analysis were performed to identify the association between the lipid profile and anthropometric parameters. The difference was considered statistically significant when p values (two-tailed) were < 0.050. Result The mean values of the serum lipid parameters other than high-density lipoprotein cholesterol were found to be higher in the subjects with an above than normal BMI, waist circumference, waist-hip ratio, waist-height ratio, and neck circumference. Pearson’s correlation coefficient and multiple regression analysis showed that waist-height ratio best predicts serum triglycerides (β=0.622, p < 0.001) and high-density lipoprotein cholesterol (β=-0.711, p < 0.001) among all measured anthropometric parameters. Conclusion Among all the studied anthropometric parameters, the WHtR was found to be the most powerful predictor of serum triglycerides and high-density lipoprotein cholesterol.